A harmonic injection method for improving NVH performance of permanent magnet synchronous motor. Issue 3 (March 2021) - Zhang, Nian; Sun, Chao; Liu, Jing; Xiong, Fei
Abstract: A harmonic injection method is proposed for reduce permanent magnet synchronous motor torque ripple and noise, which is based on harmonic model of PMSM. The effectiveness of the method is verified by simulation and experiment. It is proved that this method can significantly improve NVH performance of the motor.